Structuration of Medical Record Management During The Transition Period at Surakarta Orthopedic Hospital - Haryanti, Susi; Imbaruddin, Amir; Sudrajat, Agus; Suwarno, Yogi (Library and Information Science Study Program, Faculty of Humanities, Univ. Diponegoro, 2025)
Background of the study: This research describes the successful implementation of electronic medical record management during the transition period in Soeharso Orthopedic Hospital, Surakarta (RSO). This hospital is a specialized orthopedic hospital and is a national referral hospital. As a referral hospital, the hospital must provide maximum service to patients. The success of Electronic Medical Record (EMR) management during this transition period can be used as a reference for other hospitals in managing their medical record archives.Objective: to analyze the management of medical records during the transition from manual medical records to electronic medical records.Methods: This research uses qualitative approach with a case study design. Data sources come from interviews, FGD, observation and documentationResults: The success of medical records management in RSO during the transition period is not only determined by the availability of existing technology and policies, but also by the agent's ability to adapt and play an active role in forming a supportive structure.Conclusion: The success of RM management during the transition period is influenced by factors such as training and mentoring; management support; agent involvement in decision-making and the flexibility of the RSO organization.